THE HUMAN CONDITION IN THE 21ST CENTURY: BODY AND ARCHITECTURAL SPACE IN CONTEMPORARY ART - Sözer, Cansu; Boyacıoğlu, Can (My University, 2024)
Architectural practices that sustain economic power structures often overlook the complexity of place, prioritizing rationality and utility for funding while perpetuating issues like climate crises and income inequality. In contrast, art offers critical perspectives unconstrained by immediate practicality. This research examines how contemporary artists understand and create space to reach a spatial design approach that activates subjects and fosters new connections between humans and non-humans. In the scope of this research, seven contemporary artists who produce artworks related to either the body or space have been chosen. The discourses of artists exploring the body-space relationships serve as primary sources. Two methods are employed: logical argumentation and analysis by analogy. The latter involves visualizing the analysis of textual discourses through messy word maps to extract insights from artists’ concepts and tactics. “Artist topographies” contribute to a collective “cognitive topography,” revealing commonalities around themes of exploitation, oppression, profit, borders, otherness, agency, and complexity. The conclusion presents suggestions for an alternative spatial design approach based on the discourses and cognitive topography.
Keywords: Posthumanism; Deconstruction; Contemporary Art; Body; Theory of Architecture